Unemployment and separation: Evidence from five European countries - Anne Solaz; Marika Jalovaara; Michaela Kreyenfeld; Silvia Meggiolaro; Dimitri Mortelmans; Inge Pasteels (University of Bamberg press, 2022)
Since the 1970s, several European countries have experienced high union dissolution risk
as well as high unemployment rates. The extent to which adverse economic conditions are
associated with union instability is still unknown. This study explores the relationship
between both individual and aggregate unemployment and union dissolution risk in five
European countries before the recent economic crisis. Using rich longitudinal data from
Belgium, Finland, France, Germany, and Italy, the empirical analysis, based on discrete-
time event history models, shows that male unemployment consistently increases the risk
of union dissolution. While a strong association is observed between male unemployment
and separation at the micro level, no association is found between male unemployment
and union dissolution at the macro level. The results for female unemployment are
mixed, and the size of the impact of female unemployment is smaller in magnitude than
that of male unemployment. In Germany and Italy, where until very recently work has
been less compatible with family life than in other countries, female unemployment is not
significantly associated with union dissolution